Environmental Health Implementation Strategies in GEDSI-Friendly Health Facilities: Towards Inclusive and Equitable Services - Stella Maris Bakara; Nur Annisa Fauziyah nur; Nabila Aulia Tsaqifah3 Nabila; Bayu Pratama Tarigan Bayu (Tadulako University, 2025)
Inclusive health services are vital for ensuring equitable access, especially for vulnerable groups such as women, persons with disabilities, the elderly, and children. However, environmental health (Kesling) strategies in many health facilities still emphasize technical aspects, often neglecting gender, disability, and social inclusion (GEDSI). This qualitative study aimed to explore GEDSI-responsive Kesling strategies through Focus Group Discussions (FGDs) involving 33 environmental health officers from various institutions. Data were collected from group discussions, observational notes, and documentation of strategy proposals. Using thematic analysis, researchers identified key ideas and categorized them into three main themes: (1) gender responsive; (2) disability inclusive; and (3) socially inclusion. Proposed interventions included gender-neutral toilets, menstrual hygiene facilities, wheelchair access, child-friendly waiting rooms, and inclusive health education. The study demonstrates that FGD is an effective method to elicit grounded insights and collaborative strategies. It concludes that integrating GEDSI principles into environmental health planning requires not only technical adjustments but also inclusive dialogue with stakeholders.